2012
DOI: 10.1111/j.1365-2230.2012.04395.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse events associated with heparin

Abstract: SummaryHeparin use is associated with various cutaneous reactions, with the most common being immune-mediated skin lesions and bleeding complications. In this review, we compile the dermatological side-effects of heparin reported in the literature, and provide a clear approach to their adequate management. Heparin use and mechanism of actionHeparin (and its analogues) and warfarin are the traditional anticoagulants used for the prevention and treatment of thromboembolic disease. Table 1 shows a simplified clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
(37 reference statements)
2
10
0
Order By: Relevance
“…1 Risk factors for hypersensitivity include obesity, female sex, pregnancy, and prolonged treatment. 6 Our case series confirms literature data regarding sex and obesity, as all of our patients were female, and four of them had a body mass index of >30. These data suggest that hormonal and metabolic features are predisposing factors for heparin hypersensitivity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…1 Risk factors for hypersensitivity include obesity, female sex, pregnancy, and prolonged treatment. 6 Our case series confirms literature data regarding sex and obesity, as all of our patients were female, and four of them had a body mass index of >30. These data suggest that hormonal and metabolic features are predisposing factors for heparin hypersensitivity.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of heparin‐induced skin lesions is reported to be up to 7.5% in treated patients, with DTH being the main cause . Risk factors for hypersensitivity include obesity, female sex, pregnancy, and prolonged treatment . Our case series confirms literature data regarding sex and obesity, as all of our patients were female, and four of them had a body mass index of >30.…”
Section: Discussionsupporting
confidence: 84%
“…However, CSVV associated with warfarin and heparin has been described and attributed to immune-complex deposition. 15,16 In the pivotal DOAC trials, vasculitis adverse events including CSVV were reported in patients treated with DOACs. For example, in the ROCKET-AF trial (7111 patients treated with rivaroxaban) the incidence of cutaneous vasculitis in the rivaroxaban arm was low (0.01%).…”
mentioning
confidence: 99%
“…Research exploring the pathogenesis of DOAC‐associated CSVV is lacking. However, CSVV associated with warfarin and heparin has been described and attributed to immune‐complex deposition 15,16 …”
mentioning
confidence: 99%
“…Literature exploring the pathophysiology of rivaroxaban‐associated vasculitis is lacking. However, IgA cutaneous vasculitis associated with heparin has been described and attributed to immune‐complex deposition . Rivaroxaban‐associated immune‐complex formation and deposition in the glomerulus is a potential mechanism for IgA nephropathy observed in this case.…”
mentioning
confidence: 73%